Analisa Dampak Kegiatan Usaha Hulu Migas terhadap Ekonomi Migas di Indramayu - Dzikri Walisyah Jamal; Edy Soesanto; Rizky Andreanusa; Bismaka Daniswara (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The oil and gas sector, particularly the upstream segment involving exploration and production, plays a crucial role in contributing to Indonesia's economy. Indramayu Province, being one of the country’s oil and gas-producing areas, also experiences both direct and indirect effects from upstream oil and gas operations. This study aims to assess the influence of upstream oil and gas activities on the local economy in Indramayu Province. The research employs both qualitative and quantitative methods, incorporating secondary data analysis and interviews with relevant stakeholders. Findings indicate that upstream oil and gas operations have a substantial impact on the regional economy, notably through job creation, improved income levels, and effects on other economic sectors. However, challenges remain regarding the sustainability of natural resources and the need to better optimize the benefits for local communities. Keywords: Upstream Oil and Gas Operations, Local Economy, Indramayu Province, Economic Impact, Resource Sustainability, High-quality Oil